Creative teaching mathematics in the primary classroom - Briggs, Mary (Mary J.); Davis, Sue 1958- (London Routledge/Taylor & Francis Group, 2015)
"This stimulating text shows how primary mathematics can be creative, exciting and enjoyable. Offering teachers a dynamic and different perspective, it enables them to see and teach in creative ways that will develop their pupil's mathematical thinking potential. Creative Teaching: Mathematics in the Primary Classroom encourages students, trainees and practicing teachers to envision and develop a classroom where children can take risks, enjoy and experiment with mathematical thinking, and discover and pursue their interests and talents in an imaginative yet purposeful way. This second edition contains key updates to reflect the changes to the primary curriculum and includes: - new sections on: specialist teaching, parental engagement and approaches to homework; - creative classroom environments; - working walls, displays and outdoor settings; - links to assessment, speaking, listening and learning theory; - use of media, film, news and stories for creative learning; - cross-curricula work"--Provided by publisher.
"A David Fulron book."--Cover.
Revision of: Mathematics in the early years and primary classroom. 2008.
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching (Elementary); Mathematics -- Study and teaching (Early childhood)